Environment of European Last Mammoths: Reconstructing the Landcover of the Eastern Baltic Area at the Pleistocene/Holocene Transition - Ivan Krivokorin; Anneli Poska; Jüri Vassiljev; Siim Veski; Leeli Amon (Land)
The Eastern Baltic area stands out as a unique location due to the finds of Europe’s youngest dated mammoth remains (12.6–11.2 ka cal BP). Our study explores the drastic climate and landcover changes during the extinction of these gigantic herbivores at the Pleistocene/Holocene boundary. We used macrofossil analysis to determine the major contemporary terrestrial plant genera present in the area and used corresponding pollen taxa for REVEALS model-based landcover reconstructions. Our results indicate that these last mammoths utilised the open landcover of the Eastern Baltic, which developed as the continental ice sheet retreated during the termination of the last glaciation. Due to climate warming during the initial stages of the Holocene interglacial, the Eastern Baltic became speedily populated by birch and pine forests. The abrupt disappearance of typical forb-dominated tundra indicators, such as Dryas octopetala, and the fast increase in tree birch marked a shift from an open, tundra-like landscape to a forested one, making the environment inhospitable for mammoths even in northernmost Estonia by the beginning of the Holocene. A comparison between the isotopic values of nitrogen (δ15N) and carbon (δ13C) obtained from mammoths’ molars from 14.3 and 11.3 to 43.5 and 39.1 ka cal BP showed that mammoths experienced a decline in the nutritional value of their diet, resulting in their demise in the Eastern Baltic.